(untitled) (Bangladesh Journal of Urology, 2020)
Introduction: Oral 5-phosphodiesterase inhibitors (PDE5-I) is the main therapeutical options in erectile dysfunction (ED). It shows good results, but non-responders lack other effective options and its effect is also not long lasting. Since last few years, low-intensity extracorporeal shockwave therapy (Li-ESWT) in the corpora cavernosa showing promising results. This article presents our early experiences in Advanced Center of Kidney disease and Urology (ACKU) with the aim to evaluate clinical efficacy of Li-ESWT. Materials and methods: Thirty four patients with ED were prospectively included in the study during the period of January 2018 to Jun 2019.Treatment was performed using the PiezoWave2 (Richard Wolf, Germany) device with a linear probe. Treatment protocol included a weekly session for four weeks. Each session delivered 2000 shocks on the perineum plus 4000 shocks on dorsum penis with an energy flux density (EFD) of 0.160 mJ/mm2. Every patient has been re-evaluated 1.5 and 3 months after the last session. Pre- and post-procedure International Index Erectile Function – Erectile function domain (IIEF-EF) score, Erection Hardness Score (EHS) and Global Assessment Questionnaire-Question 1 (GAQ-Q1) answers were obtained. Results: Mean age of the study population was 39.4 (±12.9) years, 35.29% diabetic, 20.59% with hypertension and 55.85% smokers. Mean baseline IIEF-EF was 14.6, at 6 week post LiSWT was 16.4 (p >0.05) and at 3 months post LiSWT was 19.2 (p < 0.05). EHS was significantly improved at 3 month in comparison to baseline (p<0.05). 20.59% patients answered positively to GAQ-Q1 at 6 week and 61.76% at 3 months. IIEF-EF score change of >5 and increase of EHS >2 were observed in 62.88% and 70.59% study subjects respectively. Conclusions: Li-ESWT is a safe, harmless and repeatable treatment tool for ED with good outcomes reported. Bangladesh Journal of Urology, Vol. 23, No. 2, July 2020 p.176-180